Sugarcane Grub, Tomarus subtropicus Blatchley (Insecta: Coleoptera: Scarabacidae) - Eileen Buss (EDIS, 2005)
Nine species of Tomarus Erichson (formerly Ligyrus Burmeister) occur in the United States, only four of which occur in Florida, including T. gibbosus DeGeer, T. cuniculus (Fabricius), T. neglectus LeConte, and T. subtropicus (Blatchley). Tomarus subtropicus is native to Florida, where it is a turfgrass pest and the most important sugarcane pest. This document is EENY-318, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: December 2003.